2022
DOI: 10.36290/vnl.2022.084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medication errors in the hospital environment

Abstract: sociální a klinické farmacie Úvod: Zdravotní péče je inherentně spojena s rizikem poškození zdraví pacientů. Především pochybení spojené s farmakoterapií je častým typem hlášených nežádoucích událostí. Analýzou kořenových příčin medikačních chyb lze navrhnout efektivní preventivně nápravná opatření snižující pravděpodobnost jejich výskytu. Cílem studie bylo identifikovat důvody pochybení při podávání léčiv sestrami, popsat bariéry v jejich hlášení a přinést odhadovaný počet skutečně nahlášených pochybení. Meto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…It has found no consistent impact of the team nursing model on patient outcomes, nursing, and organizational results in terms of its effectiveness [21]. Another study carried out in the Czech Republic confirms this study findings [15]. The results of this study also point to MAEs related to the administration of generic substitutions.…”
Section: Medication Administration Errors Reported By Nursesmentioning
confidence: 49%
See 1 more Smart Citation
“…It has found no consistent impact of the team nursing model on patient outcomes, nursing, and organizational results in terms of its effectiveness [21]. Another study carried out in the Czech Republic confirms this study findings [15]. The results of this study also point to MAEs related to the administration of generic substitutions.…”
Section: Medication Administration Errors Reported By Nursesmentioning
confidence: 49%
“…Self-reporting and drawing attention to the occurrence of MAEs by nurses can serve as a suitable preventive and protective tool against further occurrences, although self-reporting errors in some cases can cause nurses to feel frustrated and stigmatized for admitting an MAE [1,14]. Brabcová et al [15] reported that MAEs were reported 777 times in the Czech healthcare system in 2020, and they found that the most common causes of MAE were name confusion (due to similar names but with different strengths of medication) and unclear medical prescription of medication in patients medical documentation. The authors also found that frequent changes in medication in medical documentation can conduce to MAEs.…”
Section: Introductionmentioning
confidence: 99%
“…Otázky spojené s bezpečností při poskytovaní zdravotní péče, do nichž je nutné zařadit i zacházení s léčivy, jsou aktuálním tématem pro laickou i odbornou veřejnost. V nemocničním prostředí je pravděpodobně každý desátý pacient hospitalizovaný v nemocnici poškozen možným pochybením zdravotnických pracovníků (1). Interní hodnocení kvality a bezpečí při poskytování zdravotní péče je jedním z pilířů bezpečného zacházení s léčivy, jeho nedílnou součástí je systém nežádoucích událostí, jehož cílem je vedle samotného nahlášení také analýza a doporučení nápravných (preventivních) opatření.…”
Section: úVodunclassified
“…Léková pochybení lze definovat jako jevy, které mohou vést k nevhodnému použití léčiva nebo poškození pacienta nebo se na nich mohou spolupodílet, ačkoliv je zacházení s léčivem pod kontrolou zdravotníka nebo pacienta (3). Sběr dat o nežádoucích událostech a jejich kvalitní analýza jsou jedním ze základních kroků managementu rizik a kontinuálního zlepšování kvality péče (1).…”
Section: úVodunclassified